2013
DOI: 10.1098/rspb.2013.1615
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity explains food sharing in humans and other primates independent of kin selection and tolerated scrounging: a phylogenetic meta-analysis

Abstract: ResearchCite this article: Jaeggi AV, Gurven M. 2013 Reciprocity explains food sharing in humans and other primates independent of kin selection and tolerated scrounging: a phylogenetic meta-analysis. Helping, i.e. behaviour increasing the fitness of others, can evolve when directed towards kin or reciprocating partners. These predictions have been tested in the context of food sharing both in human foragers and non-human primates. Here, we performed quantitative meta-analyses on 32 independent study populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
139
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 65 publications
12
139
0
Order By: Relevance
“…when hungry, were serviced more readily if their body condition was low. Reciprocal food sharing occurs also in other animals and is particularly common in primates, including humans [154]. A meta-analysis on 32 independent study populations of six primate species revealed similar effect sizes in humans and primates [154], which contradicts the frequently expressed apprehension that cognitive constraints prevent animals from showing direct reciprocity [190].…”
Section: Which Conditions Select For Reciprocity?mentioning
confidence: 83%
“…when hungry, were serviced more readily if their body condition was low. Reciprocal food sharing occurs also in other animals and is particularly common in primates, including humans [154]. A meta-analysis on 32 independent study populations of six primate species revealed similar effect sizes in humans and primates [154], which contradicts the frequently expressed apprehension that cognitive constraints prevent animals from showing direct reciprocity [190].…”
Section: Which Conditions Select For Reciprocity?mentioning
confidence: 83%
“…Despite the risk of free-riding, human societies do manage to solve this collective action problem. Reciprocity [33] and signalling of status [34,35] have been proposed as two processes that can explain why individuals hunt and share their catch despite the potential for others to shirk. Sometimes collective action problems involve overexploiting a resource rather than underproduction.…”
Section: Collective Action and Human Societiesmentioning
confidence: 99%
“…Although provisioning of the female by the male is also seen in various cooperative breeders, especially during incubation in birds [76], this provisioning is not reciprocal. The second element is systematic, reciprocal sharing of valuable foods by a local band's men [77], which is an expression of the male-bonding component of human social organization. Male bonding is also seen in chimpanzees, lions or raptors, but they show opportunistic sharing around a kill [78][79][80] rather than the transport of the quarry to a central home base and thus proactive sharing, as seen in humans.…”
Section: The Major Elements Of Cooperative Offspring Carementioning
confidence: 99%